Optimizing Individual and Team Productivity Through Effective Time Management Strategies - Karki, Binodh; Prakash, Dipesh; Suman, Bishal (Scieclouds Publishing, 2023)
This study investigates the importance of time management practices in enhancing individual and team productivity in workplace settings. Utilizing a quantitative methodology, a survey was administered to a diverse sample of employees across various industries to assess the impact of structured time management strategies specifically goal setting, planning, perceived time control, and time allocation on productivity outcomes. The results revealed significant positive correlations between effective time management practices and key productivity indicators, including task completion rates and adherence to deadlines. Analysis using Cronbach's alpha confirmed the reliability of the measurement instruments, with all sections achieving values above the threshold of 0.7. Furthermore, construct validity was ensured through the application of the validated Time Management Behavior Scale (TMBS) and alignment with recognized productivity metrics. This research contributes to the existing literature by empirically demonstrating the quantifiable effects of time management on productivity and addressing gaps in understanding the relationship between these variables. The findings underscore the necessity for organizations to implement structured time management interventions to enhance performance and efficiency, offering practical implications for workforce development. Future research should explore the long-term impacts of these practices and their applicability across different cultural contexts, as well as the potential moderating factors influencing the time management-productivity relationship.